2017
DOI: 10.1111/1460-6984.12320
|View full text |Cite
|
Sign up to set email alerts
|

Associations between expressive and receptive language and internalizing and externalizing behaviours in a community‐based prospective study of slow‐to‐talk toddlers

Abstract: In 24-48-month-old slow-to-talk children, lower receptive language scores were associated with higher internalizing behaviours. The magnitude of the association was small. For children with very poor receptive language scores, lower receptive language skills were associated with higher externalizing behaviours. Young children with low receptive language abilities may be at risk of internalizing difficulties; those with very low receptive language skills may be at particular risk of externalizing difficulties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
0
17
1
Order By: Relevance
“…Children of depressed mothers [24] or adolescents that have experienced parental differential treatments [25], children and adults from persistent or concordant drinking parents [26], children that have low receptive language skills [27] and children and adults from polygamous family backgrounds [28] are at a high risk of exhibiting externalizing behavior. Adolescence deviant peer group affiliations [29], adolescents with tattooing and body piercing [30], those having history or profile of jailed parents [31] and those that had remained impervious to behavioral corrections are at a high risk.…”
Section: Introductionmentioning
confidence: 99%
“…Children of depressed mothers [24] or adolescents that have experienced parental differential treatments [25], children and adults from persistent or concordant drinking parents [26], children that have low receptive language skills [27] and children and adults from polygamous family backgrounds [28] are at a high risk of exhibiting externalizing behavior. Adolescence deviant peer group affiliations [29], adolescents with tattooing and body piercing [30], those having history or profile of jailed parents [31] and those that had remained impervious to behavioral corrections are at a high risk.…”
Section: Introductionmentioning
confidence: 99%
“…Note that receptive and expressive vocabulary measures tend to be moderately to highly correlated (e.g. Conway et al, 2017). At age 10 children in BCS70 completed the Shortened Edinburgh Reading Test, a test of word recognition (Godfrey Thompson Unit, 1978), and at age 11 MCS children completed the BAS II Verbal Similarities, which measures 'crystallised intelligence' (Elliott, 1996).…”
Section: Additional Controlsmentioning
confidence: 99%
“…Specifically, Bichay-Awadalla et al (2019) found significant negative relations between early expressive and receptive language skills and later internalizing behaviors in preschool children enrolled in Head Start programs. In another community-based sample of children who were slow to talk, lower receptive language abilities were found to be associated with higher levels of internalizing behaviors, and lower receptive language scores were linked to higher levels of externalizing behaviors among children with very poor receptive language skills (Conway et al, 2017). Similarly, delayed expressive language skills were positively associated with externalizing behaviors in preschool children (Horwitz et al, 2003).…”
Section: Language Skills and Behavior Problemsmentioning
confidence: 99%